Bis-polyethylene glycol-functionalized imidazolium ionic liquids: A multi-method approach towards bulk and surface properties - Seidl, Vera; Bosch, Michael; Paap, Ulrike; Livraghi, Mattia; Zhai, Ziwen; Wick, Christian; Koller, Thomas Manfred; Wasserscheid, Peter; Maier, Florian; Smith, Ana-Suncana; Bachmann, Julien; Steinrück, Hans-Peter; et al. (Journal of Ionic Liquids, 2022)
Adding to the versatile class of ionic liquids, we report a new series of hydrophilic polyethylene glycol-functionalized room-temperature ionic liquids, offering interesting thermo- and electrochemical behavior as well as remarkable surface properties. A scalable and generally applicable synthetic procedure for the preparation of N,N’-bis(polyethylene glycol)imidazolium salts, generally abbreviated as [(mPEGn)2Im][A] (n = 2‒6, A = I‒, OMs‒, PF6‒, NTf2‒) was developed. These ionic liquids were studied concerning their thermo- and electrochemical properties, such as phase transition behavior, decomposition temperature, viscosity, and density, as well as electrical conductivity and electrochemical stability, using i.a. differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV). Additionally, the surface properties were investigated by angle-resolved X-ray photoelectron spectroscopy (ARXPS) and the pendant drop method. olecular dynamics simulations complement the studies and provide insight into the molecular structure of the ionic liquids and their specific orientation at the liquid-vacuum interface.<br